Successful treatment of a recurrent post-dural puncture headache with an epidural blood patch 18 months after the initial dural puncture. (November 2019) - Spring, A.; McMorrow, R.
Highlights: Post-dural puncture headache (PDPH) is incapacitating for the mother with a newborn. Epidural blood patch is an established treatment in those presenting acutely. In those with delayed or recurrent presentations, treatment strategy is less clear. We successfully treated a very late recurrent PDPH with an epidural blood patch. Abstract: Inadvertent dural puncture is a recognised complication of epidural insertion. Parturients are at increased risk of developing a post-dural puncture headache, which can be debilitating for a mother caring for a newborn infant. Epidural blood patch is an effective treatment in patients presenting acutely with post-dural puncture headaches but its efficacy in those with delayed presentation or with late recurrent post-dural puncture headache is less clear. We present the case of a woman with a recurrent post-dural puncture headache who was successfully treated with an epidural blood patch 18 months after the initial dural puncture. Patients who develop post-dural puncture headaches may remain symptomatic for some time and an epidural blood patch may be beneficial, following appropriate investigation.